2012
DOI: 10.1080/17458080.2011.616541
|View full text |Cite
|
Sign up to set email alerts
|

Structure control synthesis of iron oxide polymorph nanoparticles through an epoxide precipitation route

Abstract: Iron oxide polymorph nanoparticles (magnetite, goethite and lepidocrocite) were synthesised through a novel epoxide precipitation route. Epoxide, as a precipitating agent, induced the precipitation of iron(II) ions in the form of hydroxide through its reaction with aquocomplexes of Fe 2þ ions. The organic intermediate, which was produced from the ring-opening reaction of epoxide, functionalised the surface of the formed precipitate in situ, resulting in the minimisation of the nanoparticles' aggregation. Anoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(19 citation statements)
references
References 29 publications
0
9
0
1
Order By: Relevance
“…Fe-O stretching vibrations correlated with nano γ-Fe 2 O 3 are located at 630, 567, and 437 cm −1 [ 25 , 26 ]. The peaks at 890 and 795 cm −1 correspond to the Fe-O-H bending vibration bands, a characteristic of the α-FeOOH phase [ 27 , 28 , 29 ]. Additionally, in accordance with the DRX and Raman results, the M4 sample does not present the α-FeOOH phase.…”
Section: Resultsmentioning
confidence: 99%
“…Fe-O stretching vibrations correlated with nano γ-Fe 2 O 3 are located at 630, 567, and 437 cm −1 [ 25 , 26 ]. The peaks at 890 and 795 cm −1 correspond to the Fe-O-H bending vibration bands, a characteristic of the α-FeOOH phase [ 27 , 28 , 29 ]. Additionally, in accordance with the DRX and Raman results, the M4 sample does not present the α-FeOOH phase.…”
Section: Resultsmentioning
confidence: 99%
“…New polymorphs of various phases have been discovered as nanomaterials via colloidal routes. It has been recognized that both energetics and mechanism of formation are important for accessing the metastable phases via colloidal chemistry . For example, iron oxide polymorphs were synthesized via epoxide precipitation approach, and by changing the pH of the solution different polymorphs (magnetite, goethite, and lepidocrocite NPs) were formed . In another example, Pan et al have shown that Cu–In–S ternary phases could be synthesized in either the zincblende or wurtzite structures by changing the capping agent.…”
mentioning
confidence: 99%
“…Negligible structural changes and rearrangements of iron during maturation of ferric precipitates are also illustrated by ATR-FTIR spectra in Figure 3a. There are two strong absorbance bands at 885 and 796 cm −1 in the hydroxyl deformation region, labelled as δ(OH) and γ(OH), respectively, that can be assigned to goethite's characteristic vibrations [45,46], and provide some information on its crystallinity and substitution in mineral structures [45]. δ(OH) and γ(OH), respectively, that can be assigned to goethite's characteristic vibrations [45,46], and provide some information on its crystallinity and substitution in mineral structures [45].…”
Section: Transformation Of Iron Precipitates Under Alkaline Conditionsmentioning
confidence: 99%
“…There are two strong absorbance bands at 885 and 796 cm −1 in the hydroxyl deformation region, labelled as δ(OH) and γ(OH), respectively, that can be assigned to goethite's characteristic vibrations [45,46], and provide some information on its crystallinity and substitution in mineral structures [45]. δ(OH) and γ(OH), respectively, that can be assigned to goethite's characteristic vibrations [45,46], and provide some information on its crystallinity and substitution in mineral structures [45]. Since the vibrational bands between 1800 and 1000 cm −1 generally belong to water bending modes, the bands observed at ~1650 cm −1 can be assigned to the bending vibration of weakly adsorbed molecular water [47].…”
Section: Transformation Of Iron Precipitates Under Alkaline Conditionsmentioning
confidence: 99%